Dual fibular allograft dowel technique for sacroiliac joint arthrodesis - McGuire, Robert A; Chen, Zenggan; Donahoe, Kevin (Evidence-Based Spine-Care Journal, 2012)
Study design: Retrospective case series.Objective: To assess fusion rates in patients with sacroiliac joint (SIJ) pain following a minimally invasive technique using fibular dowel allograft.Methods: Thirty-seven consecutive patients (mean age: 42.5 years [range, 23–63 years]) with SIJ pain treated with 38 minimally invasive elective SIJ arthrodeses were retrospectively reviewed using chart and x-ray data. The fusion procedure consisted of minimal muscle stripping over the posterior SIJ and insertion of a cranial and caudal fibular dowel graft across the joint following placement of Steinmann pins. Fusion was deemed to be present when bone bridging trabeculae could be seen crossing the SIJ on either oblique x-rays or by computed tomographic scan. Patients were followed-up for a mean of 52 months (range, 24–62 months). Visual Analog Scale (VAS) was used to monitor clinical pain improvement. Results: Thirty-four patients with SIJ arthrodeses (89.5%) healed and led to substantial improvement in VAS pain scores (preoperative 9.1, postoperative 3.4) (P < .001). This improvement in VAS occurred over a 6-month period and was sustained through subsequent follow-up. Nonunion occurred in four patients with SIJ (10.5%). Each SIJ nonunion was successfully treated by secondary autogenous bone grafting and compression screw fixation.Conclusions: In patients with primary low back pain attributable to the SIJ, a minimally invasive, dual fibular dowel graft provided high rates of fusion and improved pain scores.